Strengths and weaknesses of multi-point machine turnouts - Paś, Jacek (Archives of Civil Engineering, 2026)
In many European countries, the choice of turnout control system is determined by the traditional approach implemented for years on railway lines or systems offered by railway turnout manufacturers. The paper presents a research approach to selecting the optimal switch operation control system based on the reliability parameters of track equipment for high-speed railway lines. In particular, a general, system approach to railway turnouts is necessary. The turnout is a structure equipped with diagnostic devices for the technical condition of the most important operating parameters, intelligent heating devices for the movable elements of the switch area and the crossing area with a movable nose, and standard communication interfaces to and from the turnout. The selection of a turnout control system is extremely important for improving the parameters of railway line availability and the safety of rail traffic. Statistical modelling of the control system for the switch and crossing with a movable nose was based on empirical data for each of the devices according to their safety integrity level, i.e. a measure of the number of operations before a fault occurs. The article presents the results of field tests conducted during the operation of a railway line as well as the results of stochastic tests based on the declarations of the manufacturers of railway traffic control systems, including switch point machines.